Culturally Liberative Mentorship: Developing agents for change in STEM doctoral education - Dilara Yaya-Bryson; Lisa Merriweather; Marah Lambert; Cathy D Howell; Edith Gnanadass (Adult Education Research Conference, 2024)
This research explored faculty perceptions and experiences regarding mentoring racially minoritized doctoral students in STEM. Cultivation of Culturally liberative mindset is recommended to guide faculty development in mentoring.
Keywords: culturally liberative mentoring; STEM; Doctoral Education; racially minoritized